Comparative study of puncture cytology and extemporaneous biopsy in the diagnosis of thyroid nodules. - Delgado, Bolívar; Perrone, Luis; Iraola, María L; Salisbury, Siul; Folle, Enrique; Risi, Leonardo; Chevalier, Nelma (Cirugía del Uruguay, 1989)
Regarding a series of 77 thyroid nodles studied by puncture cytology and extemporaneous biopsy, authors compare both methods and relate them to bibliographical data. They conclude that extemporaneous biopsy obtains very good results in our country, which do not justify it being replaced by cytology as other authors propose.